Attitudes and experiences with termination of pregnancy among Irish obstetrics & gynaecology trainees in the context of recent legal change: A survey study - Bianca M. Stifani (Elsevier, 2022)
Objective: This study examines Irish obstetrics and gynaecology trainees’ experiences with and opinions of termination of pregnancy (ToP) after legal change. Study design: We invited obstetrics & gynaecology non-consultant hospital doctors (NCHDs) to participate in a web-based survey through a professional e-mail listserv. We conducted descriptive statistical analyses of responses using Stata SE Version 16. Results: A total of 102/202 (50.5%) trainees responded to the survey. Of these, 61.8% believed that ToP should be allowed on request up to 12 weeks and in limited circumstances thereafter (in line with current law), and 19.6% believe ToP should be allowed on request even after 12 weeks. Knowledge about the abortion law was high (70.6% achieved a perfect knowledge score). Since the new law came into effect, 61.8% of trainees reported participation in abortion care, though only 25.5% had performed surgical procedures. More than 75% of respondents would like to receive more training in all clinical skills related to ToP. In the future, 67.6% of respondents would be willing to provide TOP in all circumstances allowed by law. Conclusion: Irish obstetrics & gynaecology NCHDs are generally supportive of the legislation. Few trainees have performed surgical abortions, and most would like to receive additional clinical training related to ToP.